Determination of steam quality and its affecting parameters on a steam turbine / Julie Norazreen Mat Azahar - Julie Norazreen , Mat Azahar (2018)
More than 50% of the world’s electricity generation is coming from thermal power plants. Thermal power plants used the heat energy from the steam exiting the boiler to drive the turbine and cause the shaft to rotate which will generate electricity through the generator coupled at the shaft end. The most common equipment added to the system to improve the overall efficiency of the power plant are superheaters and reheaters. Superheaters and reheaters basically improved the thermal efficiency by enhancing the steam quality which means less water droplets in the steam exiting the boiler. Dry steam is preferred to achieve a high enthalpy for higher thermal efficiency and to avoid corrosion and erosion of the turbine blades which can lead to deteriorated thermal efficiency over time. In this work, the steam quality will be measured along the high energy steam flow in a small-scale steam power plant. The impact of the steam quality to the overall performance of the power plant was also discussed. Results showed that the steam temperature decreased as it leaves the boiler, increased when it enters the superheater and decreased along the way between the superheater and turbine inlet. It was also observed that the power output of turbine increased when both the boiler and turbine inlet pressure increased.